1985
DOI: 10.1007/bf00122641
|View full text |Cite
|
Sign up to set email alerts
|

Farmers participation and socio-economic effects of a watershed management programme in Central Java (Solo river basin, Wiroko watershed)

Abstract: A self-help watershed management project in the densely populated areas of Central Java, Indonesia, is discussed in terms of its achievements to combine activities to improve the physical, the social and the economic environment. Without simultaneous, weU-planned action on these three essential components the project's improvements cannot be sustained by the farmers. It was found that activities such as tree planting and maintenance, construction of soil erosion control structures and training in agroforestry-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…This agrees with the findings of Daru and Tips (1985) who reported that participation in a watershed program (with tree planting as a component) in Central Java was highly correlated with attitude (r s = 0.892) 5 . Sagwal (1993) also found that a favourable attitude towards agroforestry increased the adoption rate of agroforestry program in Kangra (Himachal Pradesh) and Srinagar (Jammu and Kashmir), India.…”
Section: Attitude Toward Farm-level Tree Growingsupporting
confidence: 91%
“…This agrees with the findings of Daru and Tips (1985) who reported that participation in a watershed program (with tree planting as a component) in Central Java was highly correlated with attitude (r s = 0.892) 5 . Sagwal (1993) also found that a favourable attitude towards agroforestry increased the adoption rate of agroforestry program in Kangra (Himachal Pradesh) and Srinagar (Jammu and Kashmir), India.…”
Section: Attitude Toward Farm-level Tree Growingsupporting
confidence: 91%
“…Social and economic factors were not discussed by the researcher. Daru and Tips (1985) have discussed the watershed management project in densely populated areas of central Java, Indonesia in terms of its achievements in combining activities to improve the physical, social and economic environment. They stated that without simultaneous, well planned action on these three essential components the projects' improvements can not be sustained by the farmers.…”
Section: -Review Of Litraturementioning
confidence: 99%
“…Vogel (1989) discusses the implications of increasing the scale of the economic analysis from the farm level to a broader social perspective, however his discussion does not cover the inclusion of externalities. Daru and Tips (1985) discuss the social and economic factors affecting farmer participation in a watershed management and agroforestry intensification project in Java which was designed to deal with these externalities, but they do not analyze the costs or benefits. In fact, in the literature it appears that few examples of this type of analysis have been applied to agroforestry projects.…”
Section: Externalitiesmentioning
confidence: 99%